“MENEGUK CITRA, MENYEDUH MAKNA” : SEIA SEKATA’S BRANDING AS A LOCAL ROASTERY IN CIREBON - Anetta Livia Khanza; Khaerudin Imawan; Aghnia Dian Lestari (CV. Adiba Aisha Amira, 2026)
Coffee is a fiercely competitive industry, and businesses are seeking to create a strong brand identity as a way to differentiate themselves. The philosophy of “harmony” is carried out in the brand name of Seia Sekata Roastery & Espresso Bar, but far less study has been conducted on the meaning and its impact on the brand's identity. This research is to analyze the role of “Seia Sekata” brand name in brand identity based on the theory brand identity of David A. Aaker and understand the meaning that is perceived by consumers. This study uses descriptive qualitative approach with purposive sampling. In-depth interviews were conducted with the owner, frequent customers, and business associates, and thematic analysis was used, with a view to source triangulation. The results show that Seia Sekata has created their brand identity through the following: through having a consistent product quality and consumption experience which builds trust with customers (brand as product); through using harmony values in organizational culture and business communication (brand as organization); through creating a warm, open and able to build emotional closeness with consumers brand character (brand as person); and through the application of brand naming which brings a sense of togetherness and meaning through the brand experience (brand as symbol). These results suggest that the brand name, Seia Sekata can be used as a business name and can also be used as a brand image for the consumers that is authentic, consistent and meaningful.